Question Number 49359 by peter frank last updated on 06/Dec/18
Answered by MJS last updated on 06/Dec/18
$$\mathrm{it}'\mathrm{s}\:\mathrm{wrong} \\ $$$${y}=\frac{\mathrm{1}}{{x}}\:\Rightarrow\:\frac{\left({x}^{\mathrm{2}} −{x}+\mathrm{1}\right)^{\mathrm{2}} }{{x}\left({x}−\mathrm{1}\right)^{\mathrm{2}} }=\frac{\left({y}^{\mathrm{2}} −{y}+\mathrm{1}\right)^{\mathrm{2}} }{{y}\left({y}−\mathrm{1}\right)^{\mathrm{2}} };\:\frac{{y}^{\mathrm{2}} }{{y}−\mathrm{1}}=\frac{\mathrm{1}}{{x}\left(\mathrm{1}−{x}\right)} \\ $$$$\mathrm{anyway}\:\mathrm{the}\:\mathrm{equation}\:\mathrm{is} \\ $$$$\left({x}^{\mathrm{2}} −\mathrm{3}{x}+\mathrm{1}\right)^{\mathrm{2}} =\mathrm{0}\:\Rightarrow\:{x}=\frac{\mathrm{3}}{\mathrm{2}}\pm\frac{\sqrt{\mathrm{5}}}{\mathrm{2}} \\ $$